Immunoglobulins Level of CMV and T.gondii Infections in Some Pregnant Women in Baghdad - Al-Saffar, Osama B.; Jwan S. Bajlan; Sama Faqry Ali (Journal of Madenat Alelem University College, 2019)
One of the most infections constitutes a critical economic and community health issue in the wide world, especially in developing countries (Cytomegalovirus and Toxoplasmosis) infection in pregnant women. Three hundred fifty specimens of blood in total (300 infected pregnant women and 50 healthy pregnant women as control) were enrolled in this study. Determined the immunoglobulin for (IgG, IgM) of CMV and T.gondii. This study focused to detect the immunoglobulins level and prevalence of CMV and toxoplasmosis infection in pregnant women to raise awareness in the care of pregnant women. The IgG and IgM antibodies for CMV and Toxoplasma were detected by Enzyme linked immunosorbent assay (ELISA). Distributing patients into three age groups (15-25, 25-40 and > 40 years). The age group 15-25 years, shows positively for CMV in 63 pregnant women while 60 pregnant women for Toxoplasma in the same age group.